DEVELOPING A 3D PAGE FLIP E-BOOK BASED ON SCIENCE LITERACY INTEGRATED WITH ISLAMIC VALUES FOR FIFTH-GRADE STUDENTS - Ahsani, Eva Luthfi Fakhru; Hanik, Elya Umi (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
In line with the swift development of technology in learning, textbooks appear to meet the need for fast and accessible information in the form of electronic books, better known as e-books. This study, therefore, aims to develop a 3D page flip e-book based on science literacy integrated with Islamic values for fifth-grade students. This study’s samples were Islamic Elementary School Miftahul Huda 02 Dawe Kudus and Islamic Elementary School (MI/Madrasah Ibtidaiyah) Al Huda Kunduran Blora. Data collection techniques used tests, interviews, documentation, and questionnaires. This study’s results were in the form of the characteristics of teaching materials for 3D page flip e-books based on scientific literacy integrated with Islamic values, including aspects of science as the body of knowledge, science as a way to investigate, science as a way of thinking, aspects of the interaction between science, technology, society, and Islamic values. The validity of the 3D page flip e-book teaching materials based on scientific literacy integrated with Islamic values was tested and resulted in very valid criteria. Based on the research results, the validity level of teaching materials obtained a mean of 85.28%, so teaching materials were categorized as very valid. Thus, teaching materials for 3D page flip e-books based on scientific literacy integrated with Islamic values effectively improved students' scientific literacy skills. Then, the similarity test of the two means revealed that the experimental class had a higher increase in cognitive learning outcomes than the control class. The implications of this research include that 3D page flip e-book teaching materials can be used as one of the innovations; developed learning can be used as a teaching tool in the learning process; assisting students in learning the 2013 curriculum can be carried out by implementing scientific literacy-based e-book teaching materials integrated with Islamic values; the availability of e-books as learning media can increase scientific literacy; students can understand science concepts and processes to apply them in everyday life with integrated Islamic values.